Respuesta :


[tex]d = 3a + 3b \\ d =3(a + b) \\ \frac{d}{3} = a + b \\ b = \frac{d}{3} - a \\ b = \frac{d}{3} - \frac{a \times 3}{1 \times 3} \\ b = \frac{d}{3} - \frac{3a}{3} \\ b = \frac{d - 3a}{3} [/tex]
The answer is b=d-3a3

Answer:

[tex]b=d-3a3\\b=\frac{d-3a}{3}[/tex]

Step-by-step explanation:

We have the expression [tex]d=3a+3b[/tex] and we have to solve it for b, this means that we have to clear b.

The first thing we are going to do is subtract 3a from both sides.

[tex]d=3a+3b\\\\d-3a=3a+3b-3a\\\\d-3a=3b[/tex]

Now we have to divide both sides of the equation in 3.

[tex]d-3a=3b\\\\\frac{d-3a}{3}=\frac{3b}{3} \\\\\frac{d-3a}{3}=b[/tex]

Then the correct answer is the second option.

[tex]b=d-3a3\\b=\frac{d-3a}{3}[/tex]

ACCESS MORE